STUDY OF MEANS OF EXPRESSING MODALITY IN ENGLISH - Xolmatov Davrbek Mavlonovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In our article, the definition of means of expressing modality in English is analyzed on scientific grounds. The English language offers various modes of expression that allow speakers and writers to convey degrees of possibility, necessity, ability, permission, and will. These modal expressions add nuance and depth to communication and allow individuals to express their attitudes, beliefs, and assessments regarding the truth or likelihood of a statement. By examining the different ways English expresses modality, we can better understand how this important aspect of language works.